Personal electronics printing via tapping mode composite liquid metal ink delivery and adhesion mechanism - Zheng, Yi; He, Zhi-Zhu; Yang, Jun; Liu, Jing (Scientific reports, 2014)
Printed electronics is becoming increasingly important in a variety of newly emerging areas. However, restricted to the rather limited conductive inks and available printing strategies, the current electronics manufacture is usually confined to industry level. Here, we show a highly cost-effective and entirely automatic printing way towards personal electronics making, through introducing a tapping-mode composite fluid delivery system. Fundamental mechanisms regarding the reliable printing, transfer and adhesion of the liquid metal inks on the substrate were disclosed through systematic theoretical interpretation and experimental measurements. With this liquid metal printer, a series of representative electronic patterns spanning from single wires to desired complex configurations such as integrated circuit (IC), printed-circuits-on-board (PCB), electronic paintings, or more do-it-yourself (DIY) devices, were demonstrated to be printed out with high precision in a moment. And the total machine cost already reached personally affordable price. This is hard to achieve by a conventional PCB technology which generally takes long time and is material, water and energy consuming, while the existing printed electronics is still far away from the real direct printing goal. The present work opens the way for large scale personal electronics manufacture and is expected to generate important value for the coming society.